Αξιολόγηση και Προτάσεις βελτίωσης της Διαχείρισης Σχολικών Μονάδων Πρωτοβάθμιας Εκπαίδευσης με το Πληροφοριακό Σύστημα Myschool. Μελέτη περίπτωσης του Νομού Αργολίδας. - Γκαρκάσουλα, Ευανθία - Ελισάβετ (Πανεπιστήμιο Πελοποννήσου, 2025)
In this paper, an attempt is made to evaluate and propose improvements to the management of primary education schools with the Myschool information system in the Prefecture of Argolis. For this reason, a qualitative approach was used to conduct the research through the method of interviews with active primary in ten education teachers. Thus, through the research, an attempt is made to investigate the professional profile of the managers, the advantages offered by the system, the improvements that could be made, the problems and challenges they face as well as the effect on the efficiency and organization of the school units.
Μ.Δ.Ε. 77
Keywords: Εκπαιδευτική τεχνολογία; Εκπαιδευτικές καινοτομίες; Πληροφοριακά συστήματα; Συστήματα αποθήκευσης και ανάκτησης πληροφοριών-Ελλάδα, Αργολίδα; Educational technology; Educational innovations; Information storage and retrieval systems-Greece, Argolis; Information systems; Myschool; Πληροφοριακά Συστήματα; Διοίκηση σχολικών μονάδων; Information Systems; Management of school units